Defense System And Method Against Cyber-Physical Attacks - Giedre Sabaliauskaite (US Patent Office, 2022)
The present disclosure generally relates to a system and method for defending a utilities system against cyber-physical attacks associated with anomalies in a physical process operative in the utilities system. The defense system comprises: a set of sensors for collecting physical data associated with the physical process; a set of controller devices for monitoring process states of the physical process based on the physical data from the sensors; a set of verification devices for monitoring the physical process based on the physical data from the sensors, the physical data enabling the verification devices to detect the anomalies based on a set of invariants predefined for the physical process; and a set of actuators controllable by the controller devices or verification devices to remedy the anomalies and regulate the physical process, thereby defending the utilities system against the cyber-physical attacks.